Principles of Osteoimmunology Molecular Mechanisms and Clinical Applications - Pietschmann, Peter; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
Osteoimmunology is a new and rapidly developing field of great importance. It deals with mechanisms and possible treatments of bone-related diseases, such as osteoporosis, rheumatoid arthritis and periodontitis, that are caused by or associated with a malfunctioning immune system. This book describes the basics of bone biology and of the immune system and provides insight into the molecular mechanisms of bone diseases. In addition, clinical data is presented and put into context with the newest research findings. It was intended for all scientists and physicians working in immunology, pathophysiology and osteology.
Keywords: Immunology; Human physiology; Cytokines; Growth factors; Immunology; Human Physiology; Cytokines and Growth Factors